"Same Room, Safe Place": The Need for Professional Safe Sleep Unity Grows at the Expense of Families. (April 2017) - Keene Woods, Nikki
There are many different professional stances on safe sleep and then there is the reality of caring for a newborn. There is a debate among professionals regarding safe sleep recommendations. The continum of recommendations vary from the American Academy of Pediatrics (AAP) Safe Sleep Guidelines to the bed-sharing recommendations from the Mother-Baby Behavioral Sleep Laboratory. The lack of consistent and uniform safe sleep recommendations from health professionals has been confusing for families but has more recently raised a real professional ethical dilemma. Despite years of focused safe sleep community education and interventions, sleep-related infant deaths are on the rise in many communities. This commentary calls for a united safe sleep message from all health professionals to improve health for mothers and infants most at-risk, "Same Room, Safe Place."